2006
DOI: 10.1111/j.1440-1681.2007.04533.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Metoclopramide and Morphine: Enhanced Antinociception and Motor Dysfunction in Rats

Abstract: 1. Opioid analgesics and anti-emetics are often used concomitantly to treat pain and nausea and vomiting in people with malignant disease. We investigated interactions between the opioid analgesic morphine and the anti-emetic metoclopramide, a dopamine D2 receptor antagonist, on nociception and gross motor function. 2. To assess for antinociceptive interactions, 11 Sprague-Dawley rats were injected intraperitoneally with morphine (5.0 mg/kg) or saline in combination with metoclopramide (0.5, 1.5 and 5.0 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Metoclopramide is suggested to potentiate morphine analgesia [19] through the interaction with opioid receptors [20] and other putative mechanisms [21]; nonetheless more recent experimental studies [22] and clinical data [23] do not support these hypotheses, which is in line with our results. However, it should be noted that conflicting results on morphine and metoclopramide analgesic interaction might be due to different dosing schedules and rat strains used in the aforementioned experimental studies.…”
Section: Discussionsupporting
confidence: 43%
“…Metoclopramide is suggested to potentiate morphine analgesia [19] through the interaction with opioid receptors [20] and other putative mechanisms [21]; nonetheless more recent experimental studies [22] and clinical data [23] do not support these hypotheses, which is in line with our results. However, it should be noted that conflicting results on morphine and metoclopramide analgesic interaction might be due to different dosing schedules and rat strains used in the aforementioned experimental studies.…”
Section: Discussionsupporting
confidence: 43%
“…Either drug alone is associated with side-effects, and it is unclear whether the combination alters the activity or the toxicity profile of either drug. The present study was conducted to evaluate potential interactions between morphine and metoclopramide, as has been suggested in some recent reports (Krenn et al 2000;Suchitra et al 2003;Kamerman et al 2007). Drug-drug interactions (DDI) can be caused by altered pharmacokinetics or altered pharmacodynamics (Pleuvry 2005;Leucuta and Vlase 2006).…”
Section: Discussionmentioning
confidence: 95%
“…One theory postulates an interaction between the two drugs via common central dopamine systems, but no direct mechanistic studies have been conducted to prove this. There are some reports of metoclopramide enhancing opioid-induced analgesia, and recent animal studies have reported such an interaction between metoclopramide and morphine (Suchitra et al 2003;Kamerman et al 2007). Whether metoclopramide alters the pharmacokinetics or pharmacodynamics of morphine is unknown.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…MID may also evoke hyperalgesia and its analgesic effects may be influenced by rats' races [32]. MET is suggested to potentiate opioid analgesia [33] through the interaction with opioid receptors [34] and other putative mechanisms [35], although experimental [36] and clinical data did not confirm these observations [37]. However, it should be noted that conflicting results on opioid and MET analgesic interaction might be due to different dosing schedules and rats races used in the aforementioned experimental studies.…”
Section: Research Wojciech Leppertmentioning
confidence: 56%